The sober revolution : appellation wine and the transformation of France - Bohling, Joseph, 1978- (Cornell University Press, 2018)
"This book inverts our understanding of French wine by showing how the celebrated regional appellation system was a deliberate capitalist strategy to take advantage of global markets, as opposed to an inherently traditional way of making and classifying wine"--